Respostas

A melhor resposta!
  • Usuário do Brainly
2014-06-05T18:43:25-03:00


Vamos lá...

a)  (x+1)²=7+x

 x²+2x+1=7+x

x²+x-6=0

Δ=1+24=25  √Δ=5

x=(-1+5)/2=4/2=2

x=(-1-5)/2= -6/2=-3      S={-3,2}

 

b) (x-2)²-x=1

x²-4x+4-x=1

x²-5x+3=0

Δ=25-12=13   √Δ=√13

x=(5+√13)/2

x= (5-√13)/2                           S= {(5-√13)/2, (5-√13)/2


c) x²=4x/5+1/5

mmc=5

5x²=4x+1

5x²-4x-1=0

Δ=16+20=36

x=(4+6)/10=10/10=1

x=(4-6)/10=-2/10=-1/5                     S={-1/5,1}


d)  x²/4-x/3+1/9=0

mmc=36

9x²-12x+4=0

Δ=144-144=0  √Δ=0

x=12/18=2/3                         S={2/3}


e) x²-3=(x-3)/6

mmc=6

6x²-18=x-3

6x²-x-15=0

Δ=1+360=361                  √Δ=19

x=(1+19)/12=20/12=5/3

x=(1-19)/12=-18/12=-3/2                S={-3/2,5/3}


f) (x²-5x)/3+1=(2x+11)/3

mmc=3

x²-5x+3=2x+11

x²-7x-8=0

Δ=49+32=81            √Δ=9

x= (7+9)/2=16/2=8

x=(7-9)/2=-2/2=-1                 S={-1,8}


UFA!!!!!

2 5 2